The Global Food Crises and the One CGIAR's Response - Abdelaziz, Fatma (International Food Policy Research Institute, 2022)
On Tuesday, June 28th, 2022, the Consultative Group on International Agricultural Research (CGIAR) centers held a seminar under the title of "the Global Food Crises and the One CGIAR's Response”, marking the start of the National Policies and Strategies (NPS) for Food, Land, and Water Systems Transformation initiative activities in Egypt. The event was hosted by the International Food Policy Research Institute (IFPRI) Egypt office in Cairo.